Analisis Pemberian Kredit Terhadap Pendapatan - Vincentia Devina; Lusy Lusy (STIE PGRI Dewantara Jombang, 2020)
This research aims to analyze the role of Rural Credit Banks (BPR) in Sidoarjo on MSME income. The number of samples in this study were 83 customers from 9 BPRs in Sidoarjo Regency in the 2019 period. This study used quantitative research methods and data processing using multiple regression. The results showed that sales and credibility affect the income of MSMEs in Sidoarjo Regency, while the provision of credit and credibility does not affect the income of MSMEs in Sidoarjo. Lending does not affect the income of MSMEs because MSMEs that have obtained credit are at a stable stage from a financial perspective, so credit provided by BPRs is not the main capital for business expansion. This research is useful as an evaluation material for BPR in providing credit to customers. The limitation of this research is when giving questionnaires during rush hour from customers, so it requires a long process in processing the data. Suggestions for further research, qualitative research needs to be done with in-depth interviews with customers, so it is more beneficial for BPR and the world economy in general.